Evaluating the Allelopathic Efficiency of the Seed Powder of Raphanus sativus L. in Controlling some Weeds Associating Phaseolus vulgaris L. (Global Journal of Science Frontier Research, 2018)
Two pot experiments were conducted in the greenhouse of the National Research Centre, Dokki, Giza, Egypt, in the two successive seasons of 2016 and 2017 to study the allelopathic potentiality of Raphanus sativus seed powder (Rssp) on Phaseolus vulgaris growth, green and dry yield as well as its effect on the growth of associated weeds i.e., Corchorus olitorius, Abelmoschus esculentus and Portulaca oleracea. Treatments were applied by the incorporation of R. sativus seed powder (Rssp) to the soil at (0. 15, 30, 45 and 60 g/kg soil). The results indicated a significant reduction in the dry weight of C. olitorius, P. oleracea and A. esculentus in comparison to their corresponding untreated control. The phytotoxic effects of (RSSP) on the three weeds dry weight reached its maximum effect (100%) at 60g / kg soil. The results also indicated that all growth parameters of P. vulgaris as well as green and dry yield were significantly increased by different (Rssp) concentrations at the two ages of growth (40 DAS and at harvest) as compared to the corresponding untreated controls. (Rssp) at 30 g/kg soil recorded the highest values as compared to their corresponding controls. The presence of glucosinolates and Phenolic compounds in (Rssp) play an important role in its natural selective bioherbicidal properties in controlling the three weeds associating P. vulgaris plants.
Keywords: corchorus olitorius; abelmoschus esculentus; portulaca oleracea; common bean; allelopathy; raphanus sativus; glucosinolates content; phenolic content